2021
DOI: 10.3390/v13102040
|View full text |Cite
|
Sign up to set email alerts
|

Feline Calicivirus Virulent Systemic Disease: Clinical Epidemiology, Analysis of Viral Isolates and In Vitro Efficacy of Novel Antivirals in Australian Outbreaks

Abstract: Feline calicivirus (FCV) causes upper respiratory tract disease (URTD) and sporadic outbreaks of virulent systemic disease (FCV-VSD). The basis for the increased pathogenicity of FCV-VSD viruses is incompletely understood, and antivirals for FCV-VSD have yet to be developed. We investigated the clinicoepidemiology and viral features of three FCV-VSD outbreaks in Australia and evaluated the in vitro efficacy of nitazoxanide (NTZ), 2′-C-methylcytidine (2CMC) and NITD-008 against FCV-VSD viruses. Overall mortalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Based on this observation, it was suggested that FCV evolution is not associated with selective competition among different strains in the cat population [ 28 ]. No association has been demonstrated between FCV capsid gene sequences or antigenic characteristics and different disease manifestations [ 10 , 26 , 33 , 34 , 35 ].…”
Section: Virusmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on this observation, it was suggested that FCV evolution is not associated with selective competition among different strains in the cat population [ 28 ]. No association has been demonstrated between FCV capsid gene sequences or antigenic characteristics and different disease manifestations [ 10 , 26 , 33 , 34 , 35 ].…”
Section: Virusmentioning
confidence: 99%
“…Outbreaks of highly virulent and often lethal FCV infection in domestic cats have been described in the United States [ 3 , 8 , 57 , 67 , 105 ], China [ 106 , 107 ] and in several European countries: France [ 58 , 59 ], Germany [ 108 ], Italy [ 109 ], Switzerland (R.H.-L. personal communication), the UK [ 64 ], and Australia [ 35 ]. A single outbreak has also been described in exotic captive felids in the United States [ 110 ].…”
Section: Clinical Signsmentioning
confidence: 99%
See 3 more Smart Citations